Ohmic baking of gluten free sponge cake: Analysis of technological and quality characteristics - Mattioli, Nicolás Gabriel (2024)
The demand of gluten-free bakery products is worldwide increasing. Simultaneously, ohmic heating is an alternative heating technology that still deserves further research and development. Therefore, the aim of this work was assessing different technological and quality characteristics of gluten free sponge cake baked by ohmic heating. A custom ohmic system was designed and built and different electric field strengths (1500, 2000 and 2500 V/m) were tested. Conventional baking was performed for comparison purposes. The conventional baking time was 24 minutes, whilst the ohmic heating time ranged from 3.51 minutes at 2500 V/m to 7.93 minutes at 1500 V/m. The ohmic system achieved significantly higher energy efficiencies, reaching nearly 60%, compared to only 4.1% for conventional baking. Additionally, specific energy consumption was significantly lower for ohmic heating. Weight loss was higher for ohmically processed samples, showing larger pores in their inner spongy structure. Ohmic heating resulted in a larger volume expansion and a cake with lower density. The remaining quality characteristics, such as color, hardness, cohesiveness, and elasticity, were not significantly different. Results demonstrated that ohmic heating is a suitable technology for baking gluten-free sponge cakes and that it is a promising technology for fast industrial baking of such products.